Prophetic Theology; The Study of Criticism and Understanding of Hadith About The Existence of Allah - Mawardi Mawardi (Al-Bukhari, 2021)
This article focuses on studying the existence of Allah in the hadith. In this study hadith is used as the subject; of course, hadith is the main text used as the basis for the study. An interesting problem in this study is that the authority of hadith as legality to explain the existence of Allah is rarely disclosed in a separate study. The reviewers and observers of theological studies generally depart from the the Qur’an, even if there is the use of hadith only to complement the study of the the Qur’an. Even though the authority of hadith (shahīh) as a second source after the Qur'an cannot be doubted anymore, moreover, for legality in theological issues that continue to develop among Muslims and non-Muslims, making hadith as a second source must be utilized. Therefore, this article is interesting because it examines the existence of Allah through the study of hadith. The goal is that ideas about theology, especially those related to the existence of Allah, can be read through hadith as a basis for rational thinking. This study analyzes hadith texts related to the theme. Because discussing hadith is closely related to issues of validity (shahihan) and understanding, this study uses the jarh wa al-ta'dil and fiqh al-hadīs approaches. jarh wa al-ta'dil is a method to measure the validity of hadith, while fiqh al-Hadis to find meanings about the existence of Allah. From the study conducted, it can be concluded that the Messenger of Allah said that Allah alone (monotheism) is not plural and existed before something that had no beginning and no end. There is not a single creature that preceded him, and Allah is eternal forever and ever. This idea is agreed upon by all scholars regarding the oneness and eternity of Allah.